GFF Guidance Note: Inclusive Multi-stakeholder Country Platforms in Support of Every Woman Every Child - Global Financing Facility (Global Financing Facility, 2018)
The aims of this paper are: 1) to highlight how multi-stakeholder country platforms, built on development effectiveness principles, in line with the globally agreed recommendations of IHP+2, can be reinforced within the framework of the Global Strategy and its supporting mechanisms and are key to the Global Strategy’s successful implementation; and 2) to lay out key considerations for new multi-stakeholder country platforms, along with the relevant mechanisms and a minimum set of standards to support the process of national coordination among actors engaged in RMNCAH. This guidance note is intended to serve as a resource for countries committed to implementing the Global Strategy. This includes the 62 high-burden, low- and lower-middle income countries that are eligible to receive resources from the GFF Trust Fund. It will build on lessons from countries that have already developed or are currently developing prioritized RMNCAH Strategies or Investment Cases (IC)4 aligned with their broader national health plans and planning cycles and processes, for purposes of mobilizing resources, including from the GFF Trust Fund and other sources of funding. The GFF, H6 and PMNCH seek to bring together a broad set of partners and leverage their unique roles, comparative advantages and value added to maximize impact for improved outcomes for women, children and adolescents.
Keywords: #Policy Document / Documento de Política; *indexed; *tagged; G - Rest of the World / Resto do Mundo; GFF (Global Financing Facility); Health PEA; L - english / inglês; civil society / sociedade civil; development partners / parceiros de cooperação; gender / género; health / saúde; youth / juventude

Afrobarometer Round 7. Summary of Results for Mozambique, 2018 - Ipsos Mozambique (Ipsos Mozambiqu, 2018)
Afrobarometer is a pan-African, non-partisan research network that conducts public attitude surveys on democracy, governance, economic conditions, and related issues in countries across Africa. Six rounds of surveys were conducted between 1999 and 2015, and Round 7 surveys are being carried out in 2016-2018. Afrobarometer conducts face-toface interviews in the language of the respondent’s choice with nationally representative samples of 1,200 or 2,400 respondents. Afrobarometer is produced collaboratively by social scientists from across Africa. Coordination is provided by the Center for Democratic Development (CDD) in Ghana, the Institute for Justice and Reconciliation (IJR) in South Africa, the Institute for Development Studies (IDS) at the University of Nairobi in Kenya, and the Institute for Empirical Research in Political Economy/School of African Economics (IERPE/ASE) in Benin. Michigan State University (MSU) and the University of Cape Town (UCT) provide technical support to the network.
Keywords: G - Mozambique / Moçambique; L - english / inglês; M - survey / inquérito; civil society / sociedade civil; governance / governação

GFF Implementation Plan for the Gff Civil Society Engagment Strategy - Global Financing Facility (Global Financing Facility, 2017)
The implementation plan for the civil society engagement strategy (CSES) is developed to provide civil society organizations in countries (CSOs) with an operational framework to strengthen their engagement in the GFF process with a view to supporting the achievement of the objectives of the GFF and national investment cases. The plan reflects and builds on, and should be read in conjunction with the CSES. It is shaped and informed by GFF country implementation experiences to date, 12345 as well as the results of a targeted 2017 survey sent to CSOs working in GFF countries. The survey was geared towards understanding: 1) the civil society landscape in countries; 2) the level of knowledge of the GFF processes by CS; 3) priority actions CS can take to strengthen their engagement in the GFF processes and to support the achievement of the RMNCAH investment cases; and 4) what resources CS might need to better engage with national platforms and planning processes and to implement the identified supportive actions. The survey was sent to 18 organizations in 12 GFF countries and had a 61% response rate.
Keywords: #Policy Document / Documento de Política; *indexed; *tagged; G - Rest of the World / Resto do Mundo; GFF (Global Financing Facility); Health PEA; L - english / inglês; civil society / sociedade civil; development partners / parceiros de cooperação; health / saúde

EU & Partners' Country Roadmap for Engagement with Civil Society: 2016-2019 - Government of Canada; Government of Switzerland; UNICEF; USAID (Governments of Canada, Switzerland, UNICEF, USAID, 2015)
Study commissioned by EU and other countries on CSO engagement. The identification of priorities is based on four criteria: • The findings of the recent mapping of civil society in Mozambique commissioned by the EU and other studies; • The official EU guidance on the preparation of a civil society roadmap; • Existing and planned EU interventions and of the partners engaged in the roadmap; • The need to combine a longer term perspective with concrete actions over the next 3 years. The priorities constitute primarily a common agenda that will shape and orient discussions and collaboration between the roadmap partners. It allows situating individual interventions in a broader collective framework and as such adds a strategic dimension to programming.
Keywords: #Policy Document / Documento de Política; G - Mozambique / Moçambique; L - english / inglês; civil society / sociedade civil; development partners / parceiros de cooperação

Mapping study of Civil Society Organisations in Mozambique - Topsøe-Jensen, Bente; Pisco, Alice; Salimo, Padil; Lameiras, João (ALTAIR Asesores and Agriconsulting. S.L, 2015)
The Mapping Study of Civil Society Organizations (CSOs) in Mozambique was carried out during the first half of 2015, within the context of preparation for the Roadmap of the European Union (EU), Member States and other partners for engagement with civil society. Data collection included document analysis, and interviews with CSOs, international partners and Mozambican government institutions at national, provincial, district and local level. In the first phase of the field work, nine provincial workshops were held, and in the second phase four workshops were held for verification of findings and validation of recommendations. The overall objective of the mapping study is to provide the EU and all interested parties with a comprehensive overview of the state of CSOs in Mozambique, including identification of their needs and proposals for maximizing their influence in the definition and monitoring of public policies. The study also presents recommendations on the priorities to include in the EU Roadmap for engagement with civil society, and may thus contribute to improving the strategy for support to CSOs within current programming. The specific objectives are to: - Analyse the global state of play of the civil society in Mozambique, particularly regarding the environment, structure, capacity, engagement and sustainability of its organizations; - Identify existing the gaps, the fundamental needs and the opportunities for the CSOs to get involved in and influence policy processes, to monitor implementation of state commitments, and in general to claim transparency in public processes and good governance; - Provide specific recommendations on how to better meet needs identified by suggesting priorities and actions for programmes and other civil society support interventions.
Keywords: G - Mozambique / Moçambique; L - english / inglês; civil society / sociedade civil

Mid-Term Review of the AGIR Programme. Final report. - Kelpin; Johnsen, Vibe; Macuane, José Jaime; Christoplos, Ian; Rothman, Jessica (Decentralised Evaluation, 2013)
This mid-term review report of the ‘Action Programme for Inclusive and Responsible Governance’ (AGIR) in Mozambique was carried out from August 2012 to its completion at the end of October 2012 by a three-member review team fielded by Indevelop. A presentation of the preliminary findings was made on October 24th, 2012 to AGIR intermediaries and AGIR CSO partners. Subsequent to this presentation, the review team was provided with the just-completed 2012 semi-annual report, which was written and submitted jointly by AGIR intermediary organisations. AGIR has duration of five years beginning in 2010 and ending in 2014. Sweden is the only core donor, with Denmark and the Netherlands also providing support to participating INGOs (International Non-Governmental Organisations). The programme works with both national partners and with organisations in the provinces. In an effort to strengthen civil society and civil society organisations within Mozambique, the Swedish Embassy initiated the AGIR programme in 2010. The objective of AGIR is to: Support Mozambican civil society organisations, strengthening their capacity for and impact on improving transparency, accountability, citizen’s participation, access to information, respect for human rights, and gender equality. In line with the Paris Declaration and the Accra Agenda for Action, AGIR is structured to provide “good donor-ship” through support given for CSO ‘core funding’ that is aligned with the “strategic direction of the organisation” and to support and facilitate linkages and knowledge sharing between Mozambican CSOs.2 The main support modality for this capacity strengthening of CSOs is to “work through a limited number of qualified intermediary organisations within the following four clusters of support: i) Participation, social and legal accountability, including monitoring of respect for human rights; ii) Social accountability in management of natural resources and community land rights; iii) Transparency, financial and political accountability; and, iv) Promotion of access to information.”
Keywords: G - Mozambique / Moçambique; L - english / inglês; civil society / sociedade civil

Support to Civil Society Engagement in Policy Dialogue - Ministry of Foreign Affairs of Denmark (Joint Evaluation, 2013)
This evaluation, the ‘Joint Evaluation of Support to Civil Society Engagement in Policy Dialogue’ was initiated by the Donor Group on Civil Society and Aid Effectiveness. Specifically it was commissioned by three Development Partners (DPs), ADC/Austria, Danida/Denmark and Sida/Sweden, which form the Management Group. A larger group of bilateral DPs support the evaluation through their participation as the international Reference Group. The evaluation took place between June 2011 and September 2012. The Evaluation Team was drawn from the consulting firm ITAD Ltd in the UK (lead firm), together with experts from COWI (Denmark) and experts from each of the three countries selected for the fieldwork, Bangladesh, Mozambique and Uganda. The purpose of this evaluation is lesson learning, to help DPs gain a better understanding of how best to support Civil Society Organisations (CSOs) in the area of policy dialogue. The findings will also have direct relevance to the CSOs in the three countries and the wider CSO community, as well as the Governments and local authorities interacting with Civil Society (CS) representatives. The evaluation focuses on: 1. How CSOs engage in policy dialogue and the relevance and effectiveness of their policy work; 2. the enabling environment, that is the enablers and barriers to CSO engagement; and 3. how different DP support strategies may influence CSOs’ ability to engage in policy dialogue, and how best the DPs might support CSO policy dialogue in the future.
Keywords: G - Mozambique / Moçambique; L - english / inglês; M - evaluation / avaliação; citizenship & participation / cidadania e participação; civil society / sociedade civil

Afrobarometer Round 5. Summary of Results for Mozambique, 2012 - Centro de Pesquisas de Governação e Desenvolvimento (CPGD) (Centro de Pesquisas de Governação e Desenvolvimento (CPGD), 2012)
The Afrobarometer is a comparative series of public attitude surveys that will be covering up to 35 African countries in Round 5 (2011-2013). Based on representative national samples, the surveys assess citizen attitudes to democracy and governance, markets, and civil society, among other topics. The first round of surveys was conducted between 1999-2001 and covered seven Southern African countries (Botswana, Lesotho, Malawi, Namibia, South Africa, Zambia and Zimbabwe), three countries in West Africa (Ghana, Nigeria and Mali) and two in East Africa (Uganda and Tanzania). Round 2 surveys were completed by November 2003 with four new countries added: Kenya, Senegal, Cape Verde and Mozambique. Round 3 surveys were conducted from March 2005 to February 2006 in the same countries, plus Benin and Madagascar. The 4th Round of surveys covered 20 countries between 2008 and 2009, with the addition of Burkina Faso and Liberia.
Keywords: G - Mozambique / Moçambique; L - english / inglês; M - survey / inquérito; civil society / sociedade civil; governance / governação

Citizen voice and state accountability: towards theories of change that embrace contextual dynamics - Tembo, Fletcher (Overseas Development Institute, 2012)
The development industry is increasingly pushing practitioners to achieve results, and to do better in demonstrating what works, what does not, and explaining why. There is a growing interest in going beyond the measurement of results to being able to understand the basis for success or failure. Consequently, the development of explicit theories of change (ToCs) is starting to be viewed as central to this process, as a key part of what constitutes ‘rigour’ in impact evaluations. Citizen voice and accountability (CV&A) project interventions produce and reproduce diverse outcomes that are not amenable to linear models of ToCs. This paper uses a critical analysis of CV&A cases from the Mwananchi Governance and Transparency Fund (GTF) programme to examine how citizen voice and accountability happens in different governance contexts. The analytical framework used in this paper draws on the well-known tools of outcome mapping (OM) and political economy analysis (PEA). Key points: Enabling citizens to influence government accountability is a complex process involving political dynamics at the citizens’ interface with state institutions; Developing explicit theories of change (ToCs) from the start of programme planning helps planners delve into complex citizen–state dynamics; and Fusing political economy analysis and outcome mapping tools can help develop a deeper understanding of these dynamics to generate more effective ways to achieve outcomes.
Keywords: #Reviews & Framing / Revisões e Organização; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); accountability / responsabilização; civil society / sociedade civil